Specific Reactions of RSNO, HSNO, and HNO and Their Applications in the Design of Fluorescent Probes - Wang, Yingying (Chemistry, 2020)
Nitric oxide (NO)-derived species play essential roles in regulating cellular responses. Among these species, S-nitrosothiols (including RSNO and HSNO) and nitroxyl (HNO) are especially interesting. Owing to their high reactivity and short survival time, the detection of these molecules in biological settings can be challenging. In this regard, much effort has been invested in exploring novel reactions of RSNO/HSNO/HNO and applying these reactions to develop fluorescence probes. Herein, reported specific reactions of RSNO/HSNO/HNO are summarized and strategies used in the design of fluorescent probes are illustrated. The properties and potential problems of representative probes are also discussed.